2008
DOI: 10.1097/aog.0b013e318187eb2a
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Ultrasonographic Fetal Weight Estimation in Twin Pregnancies

Abstract: The accuracy of the ultrasonographic estimated fetal weight seems to be lower for twin gestations than for singleton gestations, especially for second twins. These data should be considered by clinicians when making decisions based on ultrasonographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 14 publications
8
20
1
4
Order By: Relevance
“…Our study showed that the UVVF of the IUGR twin was significantly smaller than the AGA twin (Table 2), which provides stronger evidence than other studies using singleton to study the UVVF in the IUGR fetus. We use estimated fetal weight to normalize the UVVF as in Table 2, but the accuracy of the ultrasonographic estimated fetal weight had been reported as to be lower for twin gestations than for singleton gestations (Danon et al, 2008), so potentially the normalization of UVVF by estimated fetal weight may have significant estimation bias.…”
Section: Figurementioning
confidence: 99%
“…Our study showed that the UVVF of the IUGR twin was significantly smaller than the AGA twin (Table 2), which provides stronger evidence than other studies using singleton to study the UVVF in the IUGR fetus. We use estimated fetal weight to normalize the UVVF as in Table 2, but the accuracy of the ultrasonographic estimated fetal weight had been reported as to be lower for twin gestations than for singleton gestations (Danon et al, 2008), so potentially the normalization of UVVF by estimated fetal weight may have significant estimation bias.…”
Section: Figurementioning
confidence: 99%
“…Les coefficients de corré lation retrouvé s sont assez proches des é tudes similaires, voire même meilleurs. Ainsi, Danon et al [11], avec un effectif de 278 patientes dans un dé lai de 3 jours avant l'accouchement, retrouvaient un coefficient total de 0,90 ; pour le premier jumeau R = 0,90, pour le deuxiè me jumeau R = 0,92. Le taux d'erreur é tait é galement supé rieur puisqu'ils retrouvaient un taux global d'erreur d'estimation supé rieur ou é gal à 10 % de 33,6 % pour 25 % dans notre é tude.…”
Section: Discussionunclassified
“…L'é tude de Danon et al [11] montrait que l'estimation de poids est significativement moins bonne pour le deuxiè me jumeau. Dans notre é tude, il n'est pas retrouvé de diffé rence significative dans les estimations de poids entre les jumeaux, que ce soit pour la comparaison des moyennes de diffé rence ou de la proportion d'erreur supé rieure ou é gale à 10 %.…”
Section: Discussionunclassified
See 2 more Smart Citations